FLUKTUASI HASIL TANGKAPAN IKAN PELAGIS DENGAN ALAT TANGKAP JARING INSANG HANYUT (DRIFT GILLNET) DI PERAIRAN DUMAI, PROVINSI RIAU - Damayanti, Helisha; Brown, Arthur; Sari, Ersti Yulika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on 2nd of march 2016 in Dinas Perikanan danPangkalan Pendaratan Ikan (PPI) Dumai, Riau Province. The purpose of researchfor knowing the potential of sustainable pelagis fish and analyzing the maximumof fisheries production with drift gillnet the method of research that is surveymethode. The result of research shows that the maximum of marine fisheriesproduction about 434.571 ton/year with optimum fishing effort 5571.43 trip/yearand index weight diversity of fish species in Dumai seawaters about 0.201639 thatthus H’<1 it means diversity index is low and the environment condition is notstabile.Keywords: fluctuation, pelagic fish, Dumai marine